2014
DOI: 10.4238/2014.august.7.10
|View full text |Cite
|
Sign up to set email alerts
|

Reason and treatment of failure of proximal femoral nail antirotation internal fixation for femoral intertrochanteric fractures of senile patients

Abstract: ABSTRACT. The cause of postoperative failure after the treatment of femoral intertrochanteric fracture with proximal femoral nail antirotation (PFNA) was analyzed, and the reoperative methods were examined. Nine failures of 308 femoral intertrochanteric fracture patients with PFNA were treated with femoral prosthesis total hip replacement (THR) and reoperative internal fixation. All nine patients were analyzed to determine the cause of failure. The causes of failed internal fixation in the intertrochanteric-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“… 4 In contrast, Liu et al. 28 concluded that elderly patients with osteoporosis who underwent PFNA-II fixation achieved better outcomes in the initial 3 months. Eventually, however, there were parallel outcomes of functional recovery at the final follow-up.…”
Section: Discussionmentioning
confidence: 96%
“… 4 In contrast, Liu et al. 28 concluded that elderly patients with osteoporosis who underwent PFNA-II fixation achieved better outcomes in the initial 3 months. Eventually, however, there were parallel outcomes of functional recovery at the final follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…With the rapid increase in the elderly population, the morbidity of intertrochanteric femoral fractures (IFFs) is also displaying a rising trend [ 1 3 ]. And IFFs account for approximately half the hip fractures in elderly patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In India due to better health care life expectancy has increased which lead to high proportion of older population in society, because of that morbidity of hip fracture also in raising trends [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%